The Use of Antiviral Drugs in the Treatment of Adenoviral Drugs - Abdurakhmonovich, Boboev Saidavzal; Saidavzalzoda, Abdurakhmonova Sitora (American Journal of Biomedicine and Pharmacy, 2025)
This study examines therapeutic outcomes achieved with systemic and topical antiviral agents in patients diagnosed with adenoviral ocular infection. The goal is to evaluate drug efficacy, symptom regression rate, impact on corneal complications, and overall patient recovery. Comparative assessment of different antiviral preparations provides evidence for optimized treatment protocols. This analysis evaluates therapeutic outcomes associated with antiviral medications administered for adenoviral ocular infection. The assessment focuses on clinical improvements, progression control, corneal involvement reduction, and overall recovery dynamics in patients receiving antiviral regimens compared with those who underwent supportive management alone. The findings provide evidence-based insights into treatment optimization for this highly contagious ophthalmic condition.